Isoniazid and verapamil modulatory activity and efflux pump gene expression in Mycobacterium tuberculosis - Souza, J. V. P. de; Murase, L. S.; Caleffi-Ferracioli, K. R.; Palomo, C. T.; Scodro, R. B. de Lima; Siqueira, V. L. D.; Pavan, F. R. [UNESP]; Cardoso, R. F. (Int Union Against Tuberculosis Lung Disease (i U A T L D), 2020)
INTRODUCTION: Resistance to first-line anti-tuberculosis drugs is a major concern in the treatment of the disease. New strategies, such as the use of efflux pump inhibitors (EPIs), are being investigated to improve the outcome of the treatment. Verapamil (VP), one such inhibitor, was shown to inhibit several efflux pump (EP) Mycobacterium tuberculosis proteins and demonstrate synergic activity with anti-TB drugs. OBJECTIVE: To evaluate the combinatory effect of isoniazid (INH) and VP in M. tuberculosis. METHODS: Minimal inhibitory concentrations and combinatory effects of INH+VP were determined using respectively resazurin microtitre assay plate (REMA) and resazurin drugs combination microtitre assay (REDCA). From the results, we selected three bacilli with different susceptibility profiles and assessed their expression of 10 EP genes through quantitative reverse transcription polymerase chain reaction after exposure to INH, VP and INH+VP for 48 h. RESULTS: A significant reduction of INH MIC was observed in INH-susceptible isolates upon combination with VP. In brief, gene expression assays revealed expression patterns that could be correlated with each resistance profile, presence or absence of gene mutations and combinatory effect with VP. CONCLUSION: Combining VP with INH showed important results in drug-susceptible strains, and clinical trials on combined VP + anti-TB drugs should be discussed.
Keywords: drug resistance; efflux pump inhibitors; efflux pump; tuberculosis; drug synergy